Development, characterization, cytotoxicity and antitumor effect of tamoxifen-loaded solid lipid nanoparticles - Abbasalipourkabirreh, Roghayeh (2010)
Solid lipid nanoparticles (SLN) as particulate drug delivery systems were first introduced in 1990. The aim of this study was to prepare and physiochemically and biologically characterize the Tamoxifen (TAM)-loaded SLN. Four types of SLN formulation with the following compositions: SLN-01 (90% palm oil + 10% lecithin), SLN-02 (80% palm oil + 20% lecithin), SLN-03 (70% palm oil + 30% lecithin) and SLN-04 (60% palm oil + 40% lecithin) were prepared using the high pressure homogenization method. The SLNs were characterized by the particle size and polydispersity index (particle sizer), zeta potential (zetasizer), crystallinity (differential scanning calorimetry and wide angle X-ray diffraction), and ultrastructure [transmission electron microscopy (TEM)]. The particle sizes of SLN-01, SLN-02, SLN-03 and SLN-04 were 298.40 ± 11.80, 255.40 ± 3.20, 145.00 ± 3.39 and 273.00 ± 86.50 nm respectively, while the zeta potentials were -19.44 ± 60.00, -19.50 ± 1.80, -17.83 ± 10.00 and -13.33 ± 2.30 mv respectively. Thermoanalysis and X-ray diffraction analysis showed that the SLNs had lower crystallinity than bulk lipid. The SLN particles were generally round and uniform in shape. The dimensional data suggested that SLN had high quality physicochemical characteristics, which are conducive for the loading of drugs like TAM. In this study, three types of TAM-loaded SLN with the following compositions: TAM-loaded SLNa (1 mg TAM + 5 mg SLN), TAM-loaded SLNb (1 mg TAM + 10 mg SLN) and TAM-loaded SLNc (1 mg TAM + 20 mg SLN) were prepared using the homogenization and incubation techniques. The TAM-loaded SLNs were physiochemically characterized using the method described for SLN. The particle size of the TAM-loaded SLN obtained ranged from 100 to 149 nm. The round-shaped TAM-loaded SLN particles were less ordered in crystalline structure than either bulk lipid or SLN. TAM-loaded SLNc showed the highest entrapment efficiency (EE) (90.25%) and TAM-loaded SLNa showed the highest drug-loading (DL) (17.99%). In vitro drug release of TAM-loaded SLN in human plasma showed that the amount of drug released approached 10% after 11 hours of incubation. The in vitro antitumor activities of TAM-loaded SLNa against the human breast cancer cell lines (MCF-7 and MDA-MB231) determined by the MTT assay, was similar to that of free TAM. Flow cytometry analysis showed that TAM-loaded SLN like the free TAM caused a dose- and time-dependent apoptosis without cell cycle arrest of human breast cancer cells. Therefore TAM-loaded SLN has great potential in human medicine for the treatment of breast cancers. The effect of TAM-loaded SLN on LA7 cell-induced rat mammary tumor was investigated. Twenty-four rats that developed mammary gland tumors were divided into four groups of six rats each. Group I served as untreated rats and received 1 mL soy oil. The other three groups mammary gland tumor-bearing rats treated with 10 mg free TAM dissolved in 1 mL soy oil (Group II), 10 mg TAM-loaded SLN dispersed in 1 mL soy oil (Group III), and 50 mg SLN dispersed in 1 mL soy oil (Group IV). Histopathological examination of tumor from positive control rats showed necrotic epithelial cells with mitotic activity that resembled adenocarcinomas. The therapeutic efficacy of the treatment regimes were evaluated by determining tumor size, serum enzymes such as alanine transaminase (ALT), lactic acid dehydrogenase (LDH) and alkaline phosphatase (ALP)] concentrations, histopathological and ultrastructural characteristics. Free TAM and TAM-loaded SLN reduced the tumor size by 74% and 87% respectively. The ultrastructural evaluation using TEM showed characteristic morphological features of apoptosis, to include condensation and margination of chromatin, cell budding producing membrane-bound and apoptotic bodies in the tumor of TAM-loaded SLN and free TAM treated rats. Before treatment, serum analysis showed that the concentrations of ALP and LDH increased significantly (p<0.05) in all groups of mammary gland tumor-bearing rats. After treatment with TAM-loaded SLN, the rats showed decrease in serum concentrations of these enzymes. In conclusion, the study suggests that TAM-loaded SLN is suitable to be used as a new drug delivery system. It is suggested that the SLN should be further studied and developed as a chemotherapeutic drug delivery system.